Multi-regional economic impacts of recreational fisheries: Analysis of Small Sea Ranch in Gyeong-Nam Province, Korea. (October 2017) - Kim, Do-Hoon; Seung, Chang K.; Seo, Young-Il
Abstract: The economic impacts of recreational fishing in Small Sea Ranch in Gyeong-Nam (GN) province, Korea, are calculated using a multi-regional input-output (MRIO) model to overcome the weakness of a single-region IO model that ignores the spread effects in other provinces. First, multiplier decomposition analysis is conducted to substantiate the existence of strong economic linkages between GN and other provinces by calculating intra-regional effects, net closed-loop effects, net open-loop effects and spillover coefficients. Subsequently, the economic impacts from spending by anglers' visits to Small Sea Ranch are computed using a 161-sector MRIO model for each of the sixteen provinces in Korea. The results show that there exist strong relationships between the economy of GN and those of the other provinces, and that only around 68% of the economic impacts of anglers' spending on the total output in Korea accrues in GN, with the remaining impacts (32%) being accounted for in non-GN provinces. This indicates the importance of using a multi-regional framework to estimate the economic impacts of recreational fisheries for a region whose economy relies heavily on the economies of other regions.